Hermetic bag for the storage of maize: Economic perspective in different Sub-Saharan African countries, food security and greenhouse gas emissions (Presentation) - Dijkink, Bert; Broeze, Jan (2019)
The potential of hermetic bags for storage of maize in sub-Saharan African countries.